Prevalence of Carbapenem-resistant and Carbapenemase-Producing Enterobacterales in Healthcare and Community Settings in the United Kingdom: A Systematic Review and Meta-Analysis - Dr Hossam Almadhoon; Dr Winnie WY Lee; Miss Emma R Carter; Mr Ibrahim Ahmad; Dr Colin S Brown; Dr Nina J Zhu; Prof Alison H Holmes (International Journal of Infectious Diseases)
Introduction: Carbapenem-resistant Enterobacterales (CRE) and Carbapenemase-producing Enterobacterales (CPE) pose a growing threat in the UK, with increasing prevalence in recent years. CPE and CRE are associated with higher morbidity, mortality, and healthcare costs. This study aims to summarise the existing evidence on the prevalence of CRE/CPE across healthcare and community settings in the UK. Methods: A systematic review was conducted across five major databases and two preprint websites up to February 14th, 2024. Records underwent assessment in Covidence for eligibility and relevant articles were identified, screened, and included. Metadata from selected studies were extracted and methodological quality was evaluated using an adapted Newcastle-Ottawa Scale. Pooled CRE/CPE prevalence rates with 95% confidence intervals were estimated using Der-Simonian-Laird's random-effects model (p <0.05). Heterogeneity was assessed using ChI2 and I2, publication bias was evaluated using Egger's test and funnel plot, and sensitivity analyses were performed. Results: Following the screening of 1,344 records, 32 studies were included, providing data on CRE/CPE prevalence, either in carriage or infection. In healthcare settings, the overall pooled prevalence of CRE and CPE was at 1.17% (95%CI 0.29%–2.51%; I2= 99.70%; n= 171,107) and 1.06% (95%CI 0.59%–1.64%; I2= 97.60; n= 263,833), respectively. For CPE, a high pooled proportion was observed in healthcare carriage samples at 1.23% (95%CI: 0.68%–1.91%; I2= 98.10%; n= 262,524) compared to infection samples at 0.03% (95%CI: 0.00%–0.37%; I2= 0.00%; n= 888). Surveillance of CPE in healthcare facilities varied, with risk-based admission screening identifying a slightly higher CPE proportion of 1.27% (95%CI: 0.97%–1.60%; I2= 67.30%; n= 24,763) compared to universal hospital screening at 0.82% (95%CI: 0.28%–1.65%; I2= 97.90%; n= 232,033). In the community, only two studies reported CPE prevalence (0.11%; 95%CI: 0.00%–0.79%; I2= 52.60; n= 2,630) from carriage samples using point prevalence surveys, showing a relatively low prevalence. Most of the studies on CRE/CPE were England-specific (n= 27/32), including 10 in London. Discussion: Despite high heterogeneity in the reported outcomes, the results showed consistency in the sensitivity analysis for the prevalence of both CRE and CPE. In healthcare settings, CPE was more prevalent in carriage samples, often for high-risk patients, while CRE/CPE prevalence in infection samples mirrored EuSCAPE-UK and UKHSA surveillance data. Limited community and species-level data for CPE available within the literature highlight significant gaps, particularly in the post-COVID-19 period. To mitigate the increasing prevalence of CRE/CPE, further research must be prioritised on standardized diagnostic and screening methods, exploring associated risk factors, and implement effective infection prevention and control measures. Conclusion: This review provided an overview of the expected prevalence rates of CRE and CPE in different contexts, which can further support the national surveillance of CPE/CRE in the UK, enabling more targeted screening efforts for CRE/CPE detection.